PENGARUH KESADARAN LINGKUNGAN PADA NIAT BELI PRODUK HIJAU: STUDI PERILAKU KONSUMEN BERWAWASAN LINGKUNGAN - M.F. Shellyana Junaedi (Benefit Jurnal Manajemen dan Bisnis, 2015)
This study examined the causal effect of the existing relationship between green purchasing, which is attitudinal and behavioral approaches, environment consciousness, price premium, involvement and intention to green purchase. The idea implied on this research will help much in resolving problem and decision making connected to reinforce the green purchase intention. The finding implied that environment consciousness influences to price premium and consumer involvement significantly. Another finding concludes that consumer involvement significantly influence to green purchase intention. Result, based on path analysis using AMOS indicated that the model tested had an acceptable fit. The goodness-of-fit index (GFI)